Bringing college education into prisons - Scott, Robert (New directions for community colleges, 2015)
Localizing prison higher education Doran Larson -- College inside : a case study of the design and implementation of a successful prison college program Betsy Simpkins -- Community colleges and Spanish language instruction : peer pedagogy in prison Jenifer D. Drew, José Duval, James R. Cyr -- The challenges and rewards of teaching Spanish in a community college prison program Erick Nava Palomino, Lee Ragsdale -- A call for cultural democracy Daniel E. Graves -- The transformative power of Sankofa : teaching African history inside San Quentin State Prison Nathaniel B. D. moore -- Developing a prison education pedagogy Tony Gaskew -- Teaching academic writing in a maximum security women's prison Jane Maher -- Prison fine arts and community college programs : a partnership to advance inmates' life skills Larry Brewster -- College civic engagement and education behind bars : connecting community colleges, creating change Mary Rachel Gould, Gillian Harkins, Kyes Stevens